2019
DOI: 10.3390/cells8080884
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid and Lipopolysaccharide Effect on Beta Cells Proteostasis and its Impact on Insulin Secretion

Abstract: Metabolic overload by saturated fatty acids (SFA), which comprises β-cell function, and impaired glucose-stimulated insulin secretion are frequently observed in patients suffering from obesity and type 2 diabetes mellitus. The increase of intracellular Ca2+ triggers insulin granule release, therefore several mechanisms regulate Ca2+ efflux within the β-cells, among others, the plasma membrane Ca2+-ATPase (PMCA). In this work, we describe that lipotoxicity mediated mainly by the saturated palmitic acid (PA) (16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 54 publications
2
49
1
Order By: Relevance
“…BODIPY-Leu probe was synthesized according to protocols developed by our group [22]. Then, the required quantities of l-α-phosphatidylserine and BODIPY-Leu were dissolved in chloroform and mixed vigorously to obtain a clear solution.…”
Section: Fabrication Of Vesicles Composed Of Ps (30 µM) and The Fluormentioning
confidence: 99%
See 3 more Smart Citations
“…BODIPY-Leu probe was synthesized according to protocols developed by our group [22]. Then, the required quantities of l-α-phosphatidylserine and BODIPY-Leu were dissolved in chloroform and mixed vigorously to obtain a clear solution.…”
Section: Fabrication Of Vesicles Composed Of Ps (30 µM) and The Fluormentioning
confidence: 99%
“…The three branches of UPR are essential in cell homeostasis to reduce ER stress and to ensure adequate synthesis of peptides such as insulin [20]. Indeed, in several reports, we have described the effect of metabolic overload on the dysregulation of UPR arms [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study based on the OGTT observed an association between higher total fasting plasma FFA levels and lower insulin secretion in children and adults without adjustments for confounding factors (32). Some studies proved that chronic FFA-induced lipotoxicity on pancreatic islets contributed to β cell dysfunction (33,34). Therefore, a reduction in elevated plasma FFA levels might be a critical therapeutic target for obesity-related type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%